Study on Challenges in MRT RTS Link Project - Safaat, Irfan; Muhammad Faiz bin Abdul Latif,; Kwan Yong Khang, (Progress in Engineering Application and Technology, 2023)
A railway viaduct is a type of bridge that is specifically designed to carry railway tracks over obstacles such as valleys, rivers, or urban areas. It provides a continuous and elevated pathway for trains, allowing them to traverse difficult terrain or cross over existing infrastructure without interruption. Railway viaducts are critical elements of railway infrastructure and require careful engineering and design to ensure the safe passage of trains. These structures are typically constructed using materials such as reinforced concrete, steel, or a combination of both. The choice of materials depends on factors such as the span length, load requirements, and environmental conditions of the site. The design of a railway viaduct takes into account various factors, including the anticipated loads from trains, the required clearance for trains to pass beneath the structure, and the geological and geotechnical conditions of the site. As for today, there are no railway project which does not encounter any challenges included for Malaysia Railway Transit System for Rapid Transit System project between Malaysia and Singapore. This study will provide ideas on developing the terrestrial viaduct for Rapid Transit System, RTS Link and to show that the MRT RTS Link project faces a lot of challenges during the construction.